2017
DOI: 10.1038/mp.2017.232
|View full text |Cite
|
Sign up to set email alerts
|

Reconceptualization of translocator protein as a biomarker of neuroinflammation in psychiatry

Abstract: A great deal of interest in psychiatric research is currently centered upon the pathogenic role of inflammatory processes. Positron emission tomography (PET) using radiolabeled ligands selective for the 18 kDa translocator protein (TSPO) has become the most widely used technique to assess putative neuroimmune abnormalities in vivo. Originally used to detect discrete neurotoxic damages, TSPO has generally turned into a biomarker of 'neuroinflammation' or 'microglial activation'. Psychiatric research has mostly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 196 publications
7
98
1
Order By: Relevance
“…However, we measured brain TSPO density which was shown to be independent from inflammatory markers such as cytokines in the periphery or cerebrospinal fluid 9, 63 . Moreover, recent studies suggest that alteration of TSPO expression may also reflect other abnormalities including change in metabolism at the cellular level and oxidative stress 6466 .…”
Section: Discussionmentioning
confidence: 99%
“…However, we measured brain TSPO density which was shown to be independent from inflammatory markers such as cytokines in the periphery or cerebrospinal fluid 9, 63 . Moreover, recent studies suggest that alteration of TSPO expression may also reflect other abnormalities including change in metabolism at the cellular level and oxidative stress 6466 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, TSPO PET is sensitive to changes in neuroinflammatory state. However, TSPO findings are complicated by several factors [87]. First, TSPO levels do not differentiate pro- versus anti-inflammatory processes [87].…”
Section: Using Imaging To Measure Neuroimmune Biomarkersmentioning
confidence: 99%
“…However, TSPO findings are complicated by several factors [87]. First, TSPO levels do not differentiate pro- versus anti-inflammatory processes [87]. Elevated TSPO levels in this context may reflect an upregulation in either pro- or anti-inflammatory processes or both, or leukocyte infiltration.…”
Section: Using Imaging To Measure Neuroimmune Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…The translocator protein (TSPO) is an 18 kDa protein structure located on the outer mitochondrial membrane. In the brain, TSPO is expressed in microglia, astrocytes, endothelial and smooth muscle cells and even neurons (although in lower levels compared to tissues which are essential for steroid production or lipid storage and metabolism) [1,2]. Although TSPO is present throughout the brain under normal physiological conditions [3][4][5], in vitro studies have shown that TSPO expression increases in response to immune activation [6].…”
Section: Introductionmentioning
confidence: 99%